1991
DOI: 10.1139/e91-003
|View full text |Cite
|
Sign up to set email alerts
|

Trace-element and Nd isotopic variations in Early Proterozoic dyke swarms emplaced in the vicinity of the Kapuskasing structural zone: enriched mantle or assimilation and fractional crystallization (AFC) process?

Abstract: Several Early Proterozoic Hearst–Matachewan (2.454 Ga), Kapuskasing (2.14 Ga), and Preissac (2.04 Ga) dykes were emplaced within the Archean crust surrounding the Kapuskasing structural zone (KSZ). The dykes are composed of moderately to highly fractionated tholeiitic basalts (Mg number = 24–55) that exhibit trace-element characteristics similar to those of intraplate basaltic magmas or ocean–island basalts (e.g., Zr/Nb = 6–21, Zr/Y = 2–5, high TiO2 = 0.9–3.2 wt.%, and (Fe2O3)t = 12.4–18.7 wt.%). Their initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…An extended trace-element plot (Fig. 9B) demonstrates that the elements Nb, Ta, P, and Ti are depleted relative to other elements for all of the samples, a feature characteristic of magmas generated at volcanic arcs (Pearce 1982), but also observed in many continental tholeiites worldwide (Weaver and Tarney 1981;Thompson et al 1983Thompson et al , 1984Nelson et al 1990;Boily and Ludden 1991;Cadman et al 1993;Zhao and McCulloch 1993) that have been interpreted to have been derived, at least in part, from a sub-continental lithospheric mantle source. If the primary magma(s) interacted with continental crust during ascent, then the observed elemental variations imply that the assimilant had a remarkably consistent composition.…”
Section: Major and Trace-element Geochemistrymentioning
confidence: 93%
See 3 more Smart Citations
“…An extended trace-element plot (Fig. 9B) demonstrates that the elements Nb, Ta, P, and Ti are depleted relative to other elements for all of the samples, a feature characteristic of magmas generated at volcanic arcs (Pearce 1982), but also observed in many continental tholeiites worldwide (Weaver and Tarney 1981;Thompson et al 1983Thompson et al , 1984Nelson et al 1990;Boily and Ludden 1991;Cadman et al 1993;Zhao and McCulloch 1993) that have been interpreted to have been derived, at least in part, from a sub-continental lithospheric mantle source. If the primary magma(s) interacted with continental crust during ascent, then the observed elemental variations imply that the assimilant had a remarkably consistent composition.…”
Section: Major and Trace-element Geochemistrymentioning
confidence: 93%
“…Floyd 1989;Kerr et al 1996;Neal et al 1997;White et al 1999;Hauff et al 2000;Kerr et al 2000;Tejada et al 2002) or as tholeiitic to alkalic dykes and pillowed to massive subaerial flows in continental flood basalt provinces (cf. Weaver and Tarney 1981;Menzies et al 1984; Thompson et al 1983Thompson et al , 1984Waters et al 1990;Boily and Ludden 1991;Cadman et al 1993;Baker et al 1996; Baragar et al 1996;Condie 1997). Identification of ancient, Precambrian examples of flood basalts is difficult because of their commonly deformed and metamorphosed nature and, moreover, because they have undergone substantial erosion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of Palaeoproterozoic mafic dyke swarms in the map area which are not shown, both in the Superior and Southern Province. These are, however, relatively unhelpful from the point of view of geochemical comparison, since their compositions, where geochemical data are available, are typically highly variable and probably very strongly influenced by local host-rock contamination (e.g., Boily and Ludden, 1990;Nelson et al, 1990), although it has been suggested more recently that elements of primary plume signature may be preserved in Hf/Zr ratios in the Matachewan dyke swarm (Phinney and Halls, 2001). While this is less true of the Nipissing Diabases and Huronian volcanics, they are also strongly affected by combined crustal assimilation-fractional crystallisation processes, such that isotopically and compositionally primitive compositions are extremely rare in the former case (e.g., Lightfoot et al, 1993) and unknown in the latter (e.g., Jolly et al, 1992).…”
Section: Tectonic Settingmentioning
confidence: 99%